Jesus : a meditation on his stories and his relationships with women - Greeley, Andrew M., 1928-2013. (New York : Forge, 2007)
As a storyteller, Jesus often surprised his listeners with unexpected twists that challenged them to see the world in a whole new light. Father Greeley's insightful tour of the Gospels provides a fresh look at the parables that strips away centuries of false and mistaken interpretations to get at the essential truth of who Jesus really was and what he believed. Along the way, Father Greeley touches on such provocative topics as the significance of Jesus's Jewish roots, his deep and revolutionary relationship with women, The Da Vinci Code, and The Passion of the Christ. He also singles out the four greatest parables, which best illustrate the infinite love and mercy of the God whose kingdom began with Jesus and continues even today.--From publisher description.
"A Tom Doherty Associates book."
Keywords: Jesus Christ -- Parables -- Meditations